Memorandum of understanding between Universiti Teknologi MARA and Shell Malaysia Trading Sdn Bhd / Fakulti Kejuruteraan Mekanikal - Universiti Teknologi MARA, Fakulti Kejuruteraan Mekanikal (Universiti Teknologi MARA (UiTM), 2019)
UiTM and Shell will endeavour to strengthen, promote and develop cooperation on the basis of equality and mutual benefit.